Innovation and Marketing Capabilities of Small and Medium-sized Enterprises (SMEs) in Thailand - Potjanajaruwit, Pisit (International Journal of Membrane Science and Technology, 2023)
The primary objective of this study is to investigate the impact of innovation and marketing capabilities on the performance of Small and Medium-sized Enterprises (SMEs) in Thailand. The target population for this research comprises operators of SMEs within Thailand. a sample size of 130 participants was deemed suitable for this study. To address the research goals and derive meaningful insights, the researcher employed statistical methods, with a particular emphasis on Multiple Regression Analysis. The study’s findings reveal that both innovation and marketing capabilities positively impact the performance of businesses. At a significance level of 0.05, delving into the various facets of innovation capability, it was observed that capabilities in process innovation and strategic innovation play a role in enhancing business performance. However, behavioral innovation capability does not significantly influence business outcomes. On the marketing front, capabilities in distribution channels, communication, and product development positively influence business performance. In contrast, pricing capability in marketing does not have a significant impact. SMEs in Thailand can leverage these insights for effective business management, ensuring sustained competitive advantage and optimal operational outcomes.